Drying of Merbau (Intsia bijuga) Sawdust Extract: Effect of Temperature on the Quality of Natural Dye Product - Vincent Sutresno Hadi Sujoto; Sandrina Christine Michelin Silalahi; Aswati Mindaryani; Himawan Tri Bayu Murti Petrus; Edia Rahayuningsih (Indonesian Journal of Chemistry, 2023)
The textile sector leaves 80% of effluent untreated. Carcinogenic, mutagenic, and poisonous synthetic colors in textile waste streams harm the ecosystem. Biodegradable natural dyes are safer than synthetic dyes. Merbau sawdust is abundant in Papua but underutilized. Merbau wood (Intsia bijuga) has considerable tannin and dye potential. Tannin diffuses to the surface, coloring it brown in humid air or water. Merbau extract can be dried to make powdered natural dye. This study examines Merbau sawdust extract drying and natural dye quality at different temperatures. The drying process was carried out in a convective oven at 60, 75, and 90 °C. The data showed that the solid product of natural dye was already dried at 60–90 °C within 100 min. The content of tannin in the dried natural dye powder was analyzed by titration method. The tannin content in the solid product was 0.5–0.9 g tannin/g solid. The drying rate during the constant drying rate period is around 0.00137 to 0.00256 g/cm2 min. The effect of drying temperature (60 to 90 °C) on the tannin degradation is insignificant, based on the titration method and FTIR analysis.